A Systematic Review of Global Publication Trends Regarding Long-Term Outcomes of ADHD - Hodgkins, Paul; Arnold, L. E.; Shaw, Monica; Caci, Herve; Kahle, Jennifer; Woods, Alisa G.; Young, Susan (Frontiers in Psychiatry, 2012)
There is increased global recognition of attention deficit hyperactivity disorder (ADHD) as a serious medical condition with long-term consequences. Although originally conceived of as a childhood disorder, ADHD is being increasingly recognized in adults. Individual geographic regions may have specific interests and objectives for the study of ADHD. A systematic review of long-term outcomes (LTOs) in ADHD was conducted to evaluate research on ADHD LTOs on a global scale. Studies that were at least two years in duration were examined. We identified nine outcomes of interest and classified studies by specific geographical regions, age groups studied and study design by region and over time. Published studies of LTOs in ADHD have increased in all geographical regions over the past three decades, with a peak number of publications in 2008. Although many world regions have published on ADHD LTOs, the majority of studies have emerged from the US and Canada, followed by Europe. While investigators in the US and Canada were predominantly interested in drug addiction as a LTO, European researchers were more interested in antisocial behavior, and Eastern Asian investigators focused on both of these LTOs as well as self-esteem. Proportionally fewer prospective longitudinal studies and proportionally more retrospective and cross-sectional studies have been published in more recent decades. Finally, more studies focusing on ADHD in adolescents and adults have been conducted in recent years, and particularly adolescents in Eastern Asia. This systematic review analysis of publication trends in ADHD LTOs reflects geographically-based interests that change over time.